Diseño e implementación de banca móvil para la cooperativa de ahorro y crédito de la microempresa fortuna de la ciudad de Loja, con accesibilidad desde dispositivos android. - Cruz González, Natali del Cisne (2014)
The Design and Implementation of Mobile Banking for Cooperativa de Ahorro y Crédito de la Microempresa “Fortuna” with access from Android devices aims personalized service for access from any place and time, to be a new channel loyalty that would meet the needs consumer. The paper presents the titration lojana citizenship, particularly customers of COAC Fortuna, a mobile system to allow each client monitoring, verification and ongoing monitoring of banking transactions conducted by them or others solely on products associated with client. The mobile system consists of modules Vista Deposits, Terrm Deposits and Accounts, the same that will be in the mobile application that allow querying of services described below. The methodology applied in the development of the mobile system was XP (Extreme Programming), for requirements engineering was used the guide "Software Engineering, UML (Rational Unified Process) is used to model the availability of system for the creation of applications and information management on the server was used language Netbeans WSDL programming language, for interfaces designing leaned on technology as Eclipse Android SDK, the ADT plugin and emulators to test the application and as manager of Oracle Database 11g. See Accounts, Account Information, Account Movements, Consulation Polices, Information: As a result of applying this technology the "Mobile Banking Fortuna” to provide customers the COAC Fortuna services arises Policy Movements Policy, Credit Check, Credit Information, Credit Transactions, Debit Card Information and Debit Card Lock, Security : Change key mobile banking and service membership: Download Mobile App.